Peningkatan Kemampuan Pemecahan Masalah MatematikaMelalui Model Problem Based Learning (PBL) Pada Pokok Bahasan Trigonometri (PTK di kelas X SMA Muhammadiyah 1Surakarta Tahun Ajaran 2014/2015) - Vikriyah, Nikmatul, Idris Harta, M.A., Ph.D (2015)
The aim of research increased problem solving skill through the Problem Based Learning models. The type of research was action research in classroom of SMA Muhammadiyah 1 Surakarta. The subject recipier of action research was student of class X MIA 2 SMA Muhammadiyah 1 Surakarta which amounted to 38 students, and the subject of implementing measures was researcher and teacher of mathematics class X MIA 2. Techniques of data collection was done by observation, documentation, test methods, and field notes. Triangulation technique has used ensure the validity of the data. The validity Technics of check data have done by increasing students mathematical problem solving skills views of indicators: (1) Identify the elements that are known and asked before action 31,58% increased to 84,21% at the end of the action. (2) Strategy resolve the problem before action 26,32% increased to 84,21% at the end of the action (3) Explain/ corrections prior to interpret the results of action 24,68% increased to 78,95% at the end of the action. This study suggested that the application of the Problem Based Learning models can improve the ability of problem solving.